Lipid Metabolism Disorders as Diagnostic Biosignatures in Sepsis - Charlotte Birner; Patricia Mester; Gerhard Liebisch; Marcus Höring; Stephan Schmid; Martina Müller; Vlad Pavel; Christa Buechler (MDPI AG, 2024)
Critical illness causes disturbances in lipid metabolism. Here, we investigated the levels of apolipoprotein A-IV (apoA-IV), a regulator of triglyceride and cholesterol metabolism, in human sepsis. ApoA-IV (analyzed in 156 patients with systemic inflammatory response syndrome (SIRS)/sepsis) and cholesteryl ester (CE) (analyzed in 121 of these patients) were lower in patients compared to 43 healthy controls. In contrast, triglyceride (TG) levels were elevated in patients. ApoA-IV levels in plasma of the patients did not correlate with these lipids. Patients with SIRS, sepsis or septic shock had comparable apoA-IV, TG, CE and free cholesterol (FC) levels. Patients on dialysis had significantly lower CE levels, whereas apoA-IV levels did not change much. CE levels were elevated in patients with viral sepsis due to SARS-CoV-2 infection in comparison to SIRS/sepsis patients not infected by this virus. CE levels correlated negatively with procalcitonin, interleukin-6 and bilirubin, while TGs were positively associated with bilirubin and C-reactive protein. ApoA-IV, TG, CE and FC levels were not associated with bacterial infection or survival. In conclusion, this analysis suggests that CE levels decline in sepsis-related renal failure and also shows that plasma apoA-IV and CE levels are early biomarkers of sepsis.